Surveying and Mapping - Tiberius, Christian; van der Marel, Hans; Reudink, René; van Leijen, Freek (Open textbook library., 2021)
This book provides an introduction, at academic level, into the field of surveying and mapping. The book has been compiled based on hand-outs and readers written for the third-year course Surveying and Mapping, in the bachelor program Civil Engineering at Delft University of Technology. This book covers a wide range of measurement techniques, from land surveying, GPS/GNSS and remote sensing to the associated data processing, the underlying coordinate reference systems, as well as the analysis and visualization of the acquired geospatial information.